Give Me the Stars / Break of Day - Tauber, Richard 1891-1948 (United Kingdom Parlophone, 1945)
The Austrian tenor Richard Tauber made over 720 vocal recordings for the Odeon/Parlophone companies, plus several as an orchestral conductor, mainly of his own works, but also of music by Grieg and Johann Strauss, Jr.
From the motion pictures 'Give Me the Stars' (1945) and 'Waltz Time' (1945). In the last, Richard Tauber performed the role of Shepherd.
Keywords: 20th Century (1901-2000); Film; Popular music; Song; United Kingdom